2003
DOI: 10.1002/chem.200304888
|View full text |Cite
|
Sign up to set email alerts
|

2‐Phosphanylphenolate Nickel Catalysts for the Polymerization of Ethylene

Abstract: The previously unknown methallylnickel 2-diorganophosphanylphenolates (R=Ph, cHex) were synthesized and found to catalyze the polymerization of ethylene. To explore the potential for ligand-tuning, a variety of P-alkyl- and P-phenyl-2-phosphanylphenols was synthesized and allowed to react with [Ni(cod)(2)] (cod=1,5-cyclooctadiene) or with NiBr(2).DME and NaH. The complexes formed in situ with [Ni(cod)(2)] are generally active as ethylene polymerization catalysts with all the ligands tested, whereas the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 64 publications
5
106
0
Order By: Relevance
“…[7] It is stable to air at room temperature for weeks and can be handled with no special precautions. Acylation followed by silica gel filtration affords the ligation agents 4, which can be used without further purification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] It is stable to air at room temperature for weeks and can be handled with no special precautions. Acylation followed by silica gel filtration affords the ligation agents 4, which can be used without further purification.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we replaced phosphanes 1 with the corresponding monofluoro derivatives 4 (Scheme 4), which could be obtained in high yields from the known phosphane 7 [7] by reaction with the appropriate amino acids and condensing agents (Scheme 4). The functionalized phosphanes 4a-e were synthesized to examine the Staudinger ligation of the aspartic and glutamic acid side-chains (4a and 4b, respectively) as well as the reactions of simple α-and β-amino acids such as β-alanine 4c, glycine 4d and proline 4e.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] For instance, nickelexchanged zeolites play an important role in studying the mechanistic aspects of selective catalytic reduction of NO x [2] or selective hydrogenation of nitro aromatic compounds. [3] Phosphanylphenolate nickel complexes are active in olefin polymerization, [4] whereas the methanogenesis cycle is catalyzed by methylcoenzyme M (methyl-CoM) reductase with the cofactor F 430 comprising Ni I hydrocorphinoid. [5] Ni I -carbonyls of biologically relevant complexes can mimic the activity of acetylcoenzyme A synthases (acetyl-CoA) [6] or dihydrogen oxidation by hydrogenases.…”
mentioning
confidence: 99%
“…Selected bond lengths (Å) and angles ( • ): P C(1) 1.8347(17), P P#1 2.2253(6); C(1) P P#1 104.31(6), C(1) P P#2 100.86(6), P#1 P P#2 85.134(13), P C(1) C(2) 124.99(12), P C(1) C(6) 116.79 (13); symmetry transformations used to generate equivalent atoms: #1 −y + and Ni(COD) 2 (COD 1,5-cyclooctadiene) or other related isolated complexes catalyze the polymerization or oligomerization of ethylene [3,4]. Ligand tuning revealed that the polymer chain length increases for various PR 2 groups in the order Ph 2 P < PhtBuP ≈ PhiPrP < Et 2 P < tBu 2 P < iPr 2 P < cHex 2 P. This is accounted for by an increase of the chain lengths with the basicity of the phosphino groups, superimposed upon a sterically induced decrease in the case of α-branched alkyl groups [3a], and raises the question of the effect of primary and secondary phosphino groups.…”
Section: Polymerization Of Ethylenementioning
confidence: 99%
“…P-Tertiary 2-phosphinophenols have found considerable interest as ligands in transition metal complexes [1,2], and organonickel phosphinophenolate chelate complexes proved to be efficient moisturetolerant polymerization or oligomerization catalysts [1, 3,4]. P-Tertiary 2-phosphinophenol ethers became familiar by the formation of hemilabile P ∩ O-chelate complexes [5] and the use of suitable asymmetric derivatives in highly enantioselective Rh-catalyzed hydrogenation reactions [6].…”
Section: Introductionmentioning
confidence: 99%